METHODS OF READINESS DETERMINATION OF FUTURE TEACHER TO LOCAL HISTORY ACTIVITY IN THE COUNTRY - Tsukanov, M.I. (Tambov University Review. Series: Humanities, 2016)
The method of definition of history teacher’s readiness to the historical and regional studies in rural agribusiness in continuing education system is considered. The features of work in a rural school and the importance of the development of regional agricultural education are discussed. Attention is paid to the importance of local history education for rural development and agrarian business culture of pupils. There is justified the need of creation and implementation of new method in the training of university students of historical and pedagogical direction. The method was developed on the basis of existing techniques, taking into account the requirements of the research on the formation of readiness of the future teachers to the historical and regional studies in villages and consists of two parts - the survey and direct observation, which allows more fully assess the level of preparedness of students. This method takes into account various criteria for readiness to teaching in the sphere of local history, such as empathy, sociological reflection, Gnostic and constructive skills, knowledge of local history, folklore and tradition, knowledge of historical analysis methods, agrarian business-culture, communication skills and others. The result of study using the developed method is a summary sheet of readiness for the historical and regional studies.